Differences in the pregnancy gestation period and mean birth weights in infants born to Indian, Pakistani, Bangladeshi and white British mothers in Luton, UK: a retrospective analysis of routinely collected data. Issue 8 (11th August 2017) - Garcia, Rebecca; Ali, Nasreen; Guppy, Andy; Griffiths, Malcolm; Randhawa, Gurch
Abstract : Objective: To compare mean birth weights and gestational age at delivery of infants born to Indian, Pakistani, Bangladeshi and white British mothers in Luton, UK. Design: Retrospective analysis using routinely recorded secondary data in Ciconia Maternity information System, between 2008 and 2013. Setting: Luton, UK. Participants: Mothers whose ethnicity was recorded as white British, Bangladeshi, Pakistani or Indian and living in Luton, aged over 16, who had a live singleton birth over 24 weeks of gestation were included in the analysis (n=14 871). Outcome measures: Primary outcome measures were mean birth weight and gestational age at delivery. Results: After controlling for maternal age, smoking, diabetes, gestation age, parity and maternal height and body mass index at booking, a significant difference in infants' mean birth weight was found between white British and Indian, Pakistani and Bangladeshi infants, F(3, 12 287)=300.32, p<0.0001. The partial Eta-squared for maternal ethnicity was η 2 =0.067. The adjusted mean birth weight for white British infants was found to be 3377.89 g (95% CI 3365.34 to 3390.44); Indian infants, 3033.09 g (95% CI 3038.63 to 3103.55); Pakistani infants, 3129.49 g (95% CI 3114.5 to 3144.48); and Bangladeshi infants, 3064.21 g (95% CI 3041.36 to 3087.06). There was a significant association in preterm delivery found in primipara Indian mothers, compared with Indian mothers (Wald=8.192, df 1, p<0.005). Conclusions: Results show important differences in adjusted mean birth weight between Indian, Pakistani, Bangladeshi and white British women. Moreover, an association was found between primipara Indian mothers and preterm delivery, when compared with Pakistani, Bangladeshi and white British women.